A new stadium for Union Saint-Gilloise. The opinions of fans - Olivier Paye; Thomas Ermans; Thomas Laloux; Youri Lou Vertongen; Loïc Cobut; Lou Kervarrec (Brussels Studies)
For several years now, a project for a new stadium at Bempt in Forest to the benefit of Union Saint-Gilloise has been a subject of debate, with no favourable decision having been taken by the public authorities by mid-2025. This article examines the results of an online survey carried out in mid-2023 among Unionist fans to find out about their views regarding this controversy. It reveals that the idea of a new stadium is a divisive one for fans. Although a large majority are in favour, the extension of the current stadium is the preferred option, with the Bempt project coming in second place. The minority of fans who are content with the status quo and least in favour of a new stadium and the Bempt option are characterised by less active and more recent support. Despite their differing preferences, many fans agree on the importance to be given in the debate to a series of arguments both in favour of a new stadium – compliance with UEFA standards, increased capacity, contribution to the club's continued existence at a high level – and against a new stadium – risk of loss of identity and of higher ticket prices, with the issue of accessibility by public transport also pinpointed.